Open management and role in developing the innovation mindset of managers (Al-Mansour Journal, 2022)
The research aims to identify the test of the relationship between the characteristics of the management of short and innovative mental managers. The various variables witnessed by the world have shown the importance of short management and its impact on the innovative mind. The researcher tried to classify these issues in a practical way by answering the following questions: For short management at the Industrial Park in Diyala. Are there any effects of the overdraft characteristics in the innovative mind? In order to answer these questions, a default model was developed to reflect the correlation relationship, which was tested through a set of The data collected by the questionnaire is dedicated to this aspect. The research concluded on a set of conclusions that the company mentioned has intelligent systems at the administrative and technological level. The research also takes into consideration important recommendations, the most important of which are to face the obstacles and challenges represented by bureaucracy and bureaucracy
Keywords: short management; innovative mind; industrial complex in Diyala